An evaluation of home visiting of patients by physicians in geriatric medicine. Issue 6293 (12th September 1981) - Arcand, Marcel; Williamson, J
Abstract : The practice of preadmission home visiting of patients referred to geriatric medicine units has in recent years been criticised as being unnecessary on the grounds that if there is no waiting list there is no need for allocation of priority for admission; as being wasteful of doctors' time; as being resented by general practitioners; and as failing to provide adequate clinical information. The geriatric medicine department at the City Hospital with no waiting list for patients referred by general practitioners has retained home visits for most referrals because of the advantages in terms of acceptability to general practitioners (98-100%); the quantity and quality of information obtained; the usefulness of this information in deciding appropriate management and in planning discharge from hospital; and the provision of a unique teaching opportunity, which is highly valued by students and teachers alike.